Minimum Wage, Worker Quality, and Consumer Well-Being: Evidence from the Child Care Market - Jessica H. Brown; Chris M. Herbst (Institute of Labor Economics (IZA), 2023)
This paper combines multiple data sources to study the impact of the minimum wage on service quality and consumer well-being within the child care market. Although child care firms increase teacher pay in response to minimum wage reforms, we find no impact on employment levels. Instead, providers respond by implementing a range of other revenue-enhancing and cost-saving practices, such as raising prices, increasing child-to-staff ratios, and serving fewer children in the child care subsidy system. We also find evidence that service quality increases: staff turnover declines, teachers are more likely to make human capital investments, and teacher-child interactions improve. Despite the increase in quality, parents report that they are less satisfied with their child care provider, a result we attribute to the increase in prices.
Keywords: J13; J15; J21; K39; 330; child care; child care quality; minimum wage